Impact of SGLT2 inhibitors in comparison with DPP4 inhibitors on ascites and death in veterans with cirrhosis on metformin. Issue 10 (28th July 2021) - Saffo, Saad; Kaplan, David E.; Mahmud, Nadim; Serper, Marina; John, Binu V.; Ross, Joseph S.; Taddei, Tamar
Abstract: Sodium‐glucose cotransporter 2 inhibitors (SGLT2i) may have favourable neurohumoral and metabolic effects in patients with chronic liver disease. However, studies examining SGLT2i in this population have been limited to patients with non‐alcoholic fatty liver disease and have focused on surrogate biomarkers. Our aim was to evaluate whether SGLT2i can reduce the incidence of ascites and death over a period of 36 months in patients with cirrhosis and diabetes mellitus. Using electronic health data from Veterans Affairs hospitals in the United States, we conducted a propensity score matched intention‐to‐treat analysis among veterans on metformin who subsequently received either SGLT2i or dipeptidyl peptidase‐4 inhibitors. Among 423 matched pairs (in total, 846 patients), we found no significant difference in the risk for ascites (hazard ratio 0.68 for SGLT2i, 95% confidence interval 0.37‐1.25; p  = .22) but did find that SGLT2i users had a reduced risk for death (adjusted hazard ratio 0.33, 95% confidence interval 0.11‐0.99; p  < .05). In comparison with dipeptidyl peptidase‐4 inhibitors, SGLT2i may improve survival for patients with cirrhosis who require additional pharmacotherapy for diabetes mellitus beyond metformin, but confirmatory studies are necessary.